Selective extraction of proteins and other macromolecules from biological samples using molecular imprinted polymers. (November 2016) - Stevenson, Derek; EL-Sharif, Hazim F; Reddy, Subrayal M
The accurate determination of intact macromolecules in biological samples, such as blood, plasma, serum, urine, tissue and feces is a challenging problem. The increased interest in macromolecules both as candidate drugs and as biomarkers for diagnostic purposes means that new method development approaches are needed. This review charts developments in the use of molecularly imprinted polymers first for small-molecular-mass compounds then for proteins and other macromolecules. Examples of the development of molecularly imprinted polymers for macromolecules are highlighted. The two main application areas to date are sensors and separation science, particularly SPE. Examples include peptides and polypeptides, lysozyme, hemoglobin, ovalbumin, bovine serum albumin and viruses.